2020
DOI: 10.1021/acs.jnatprod.0c00642
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR-Cas9 Genome-Wide Knockout Screen Identifies Mechanism of Selective Activity of Dehydrofalcarinol in Mesenchymal Stem-like Triple-Negative Breast Cancer Cells

Abstract: There are no targeted therapies available for triplenegative breast cancers (TNBCs) in part because they represent a heterogeneous group of tumors with diverse oncogenic drivers. Our goal is to identify targeted therapies for subtypes of these cancers using a mechanism-blind screen of natural product extract libraries. An extract from Desmanthodium guatemalense was 4-fold more potent for cytotoxicity against MDA-MB-231 cells, which represent the mesenchymal stem-like (MSL) subtype, as compared to cells of othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…The copyright holder for this this version posted September 15, 2021. ; https://doi.org/10.1101/2021.09.15.460423 doi: bioRxiv preprint p.6/55 synthetic derivatives tested. In addition, HSD17B11 has been recently identified as mediating, through an unknown mechanism, the cytotoxic effect of dehydrofalcarinol, a polyacetylenic compound with a terminal butadiynylalkenylcarbinol motif isolated from several plants of the Asteraceae family (21).…”
Section: Resultsmentioning
confidence: 99%
“…The copyright holder for this this version posted September 15, 2021. ; https://doi.org/10.1101/2021.09.15.460423 doi: bioRxiv preprint p.6/55 synthetic derivatives tested. In addition, HSD17B11 has been recently identified as mediating, through an unknown mechanism, the cytotoxic effect of dehydrofalcarinol, a polyacetylenic compound with a terminal butadiynylalkenylcarbinol motif isolated from several plants of the Asteraceae family (21).…”
Section: Resultsmentioning
confidence: 99%
“…In the future, we plan to conduct additional binding studies with radiolabeled ATXII, which will be used to identify its direct molecular target(s). Additionally, a CRISPR-Cas9-mediated gene knockout screen will be employed to further define the mechanism of ATXII-induced DNA damage in ES cells [ 55 ]. Lastly, the development of an ATXII-resistant ES cell line, followed by whole-exome and RNA sequencing, would be useful in identifying both genetic and epigenetic mechanisms of ATXII resistance, and may provide further insight into its mechanisms of action.…”
Section: Discussionmentioning
confidence: 99%
“…It is shown that HSD17B11, the gene encoding the enzyme 17β-hydroxysteroid dehydrogenase type 11, was a mediator of the selective cytotoxic effects of 26a in MDA-MB-231 cells. [57] There are other natural products from terrestrial with anti-TNBC activities (Table 1) (Figure 10).…”
Section: Terrestrial Natural Productsmentioning
confidence: 99%
“…A CRISPR‐Cas9‐mediated gene knockout screen was employed to identify the mechanism of selective cytotoxic activity. It is shown that HSD17B11, the gene encoding the enzyme 17β‐hydroxysteroid dehydrogenase type 11, was a mediator of the selective cytotoxic effects of 26a in MDA‐MB‐231 cells [57] …”
Section: Natural Products With Anti‐tnbc Activitiesmentioning
confidence: 99%